Decotex Sdn. Bhd / Normala Hassim, Fatima Haris, Norsuhana Othman... [et.al]. - Othman, Norsuhana; Haris, Fatima; Othman, Norsuhana; Abas, Julia; Abdul Rahman, Rozita (Faculty of Applied Sciences, 2006)
We have agreed to choose DECOTEX SDN BHD as our name of the company. DECO means decoration and TEX means textile. So, DECOTEX means our company's innovation in textile with an up date design. We think that the mentioned name is suitable for our goals as well as to give the spirit in the business.